Developmental gene expression profiles of the human pathogen Schistosoma japonicum - McManus Donald P; Brindley Paul J; Moertel Luke; Gobert Geoffrey N (BMC Genomics, 2009)
Abstract Background The schistosome blood flukes are complex trematodes and cause a chronic parasitic disease of significant public health importance worldwide, schistosomiasis. Their life cycle is characterised by distinct parasitic and free-living phases involving mammalian and snail hosts and freshwater. Microarray analysis was used to profile developmental gene expression in the Asian species, Schistosoma japonicum. Total RNAs were isolated from the three distinct environmental phases of the lifecycle – aquatic/snail (eggs, miracidia, sporocysts, cercariae), juvenile (lung schistosomula and paired but pre-egg laying adults) and adult (paired, mature males and egg-producing females, both examined separately). Advanced analyses including ANOVA, principal component analysis, and hierarchal clustering provided a global synopsis of gene expression relationships among the different developmental stages of the schistosome parasite. Results Gene expression profiles were linked to the major environmental settings through which the developmental stages of the fluke have to adapt during the course of its life cycle. Gene ontologies of the differentially expressed genes revealed a wide range of functions and processes. In addition, stage-specific, differentially expressed genes were identified that were involved in numerous biological pathways and functions including calcium signalling, sphingolipid metabolism and parasite defence. Conclusion The findings provide a comprehensive database of gene expression in an important human pathogen, including transcriptional changes in genes involved in evasion of the host immune response, nutrient acquisition, energy production, calcium signalling, sphingolipid metabolism, egg production and tegumental function during development. This resource should help facilitate the identification and prioritization of new anti-schistosome drug and vaccine targets for the control of schistosomiasis.